Identifikasi Jenis Tumbuhan Air di Danau Sabuah Pulang Pisau Kalimantan Tengah - Rosana Elvince; Tutwuri Handayani; Maryani Maryani; Zakia Nisfi Rahmadia (Universitas Batangahari Jambi, 2023)
Aquatic plants are plants that enjoy water for part of their life cycle in water and are a part of supporting aquatic ecosystems. The presence of aquatic plants is an important factor as a supporting role, which will be controlled if the population does not exceed the limit. This study aims to determine and understand the type, density and diversity of aquatic plants. This research activity was carried out in Sabuah Lake, Pulang Pisau. The aquatic plants obtained in this activity were 6 species of aquatic plants namely water hyacinth (Eichhornia crassipes), sticky rice (Polygonum barbatum), kiambang (Salvinia molesta), para grass (Cyperus platystylis), walingi (Cyperus elatus L.) and ribbon grass ( Vallisneria americana Mich.). The method used in this research is by sampling at each station, which is done in locations that represent the conditions of Lake Sabuah. The sampling locations are divided into 3 stations, which are determined by following the topographic conditions of Lake Sabuah and the activities of the communities living around the lake. There are 3 observation points at each station. To determine the area of each sampling area, a plot made of 2x2 m pralon pipes is used. The research results show that in Lake Sabuah, there are 6 species of aquatic plants, namely water hyacinth (Eichhornia crassipes), knotweed (Polygonum barbatum), water fern (Salvinia molesta), para grass (Cyperus platystylis), walingi (Cyperus elatus L.), and tape grass (Vallisneria americana Mich). The dominant aquatic plants in Lake Sabuah are water hyacinth and water fern. The diversity and dominance values of aquatic plants in Lake Sabuah range from 0-1 (Ds) and 0.4365 (D), respectively.